The effects of short-term and long-term oriented managerial behavior on medium-term financial performance: longitudinal evidence from Europe - Brauer, Matthias F. (Journal of Business Economics and Management, 2013)
Short-term orientation aimed at maximizing quarterly results at the expense of long-term corporate performance and survival has become severely criticized. In the face of continuously decreasing chief executive officer (CEO) tenure, CEOs, however, seem to have few incentives to embrace long-term oriented behaviour. Instead, the question of foremost importance to self-interested CEOs is whether short-term orientation already harms financial performance in the three to four years of their own tenure, and whether CEOs stand a chance of benefiting from long-term orientation while still in office. CEOs thus face an intriguing ethical dilemma between optimizing their financial pay-off within their own tenure and securing the longer-term well-being of the corporation, its employees, and other major stakeholders. Consequently, our longitudinal study focuses on the medium-term performance implications of short-term and long-term orientation in Europe’s largest publicly listed companies. Results indicate that short-term orientation negatively impacts on medium term performance while long-term oriented behavior is positively associated with corporate performance in the medium term. Our findings advance managerial myopia theory, and provide insights into one of the most central ethical dilemmas faced by corporate executives today.